Edukasi Pariwisata Dan Aksi Sisir Pantai Dari Sampah Wisata Dalam Upaya Meningkatkan Partisipasi Masyarakat Di Kawasan Super Prioritas Nasional (KSPN) Labuan Bajo, Kabupaten Manggarai Barat - Mary Ismowati; Bhakti Nur Avianto; Angga Sulaiman; Anggra Liany Rihadatul Aisi; Vicky Zaynul Firmansyah (Institut Ilmu Sosial dan Manajemen Stiami, 2022)
The development and development of the tourism sector in Indonesia is growing. The determination of Labuan Bajo as a National Tourism Strategic Area makes it one of the premium tourist areas in Indonesia. Tourism development in its implementation found various obstacles and problems. We carry out community service programs in Labuan Bajo, to find out the problems and obstacles to tourism development. Our method is to conduct interviews and observe tourism locations. And we see the government's response and the community's response in an effort to maximize tourism potential in Labuan Bajo. We provide education and training regarding the utilization of tourism potential so that it has an impact and economic value. Second, we take action to clean up tourist sites and provide an understanding of how to manage waste in 3Rs (Reuse, Reduce, Recycle). The results we found, the community is still less involved in participation in tourism development, the government is still not optimal in policy regulation and utilization of tourism potential, and the biggest tourism problem occurs in poor tourism waste management.